La yuca (Manihot esculenta Crantz), alimento base de pobladores en Guyana - Beecham, Premdat (2023)
The cassava is an important phytogenetic resource in Guyana, where is the fourth nutritional product in order of importance according to the amount of calories that contains, following rice, wheat and corn. It takes part in the Guyanese populations' nutritional plans and is the primary agricultural product of the indigenous communities. The indigenous population depends on the diversity of dishes and beverages such as farinha, casabe, cassareep and piwari which are made from the root of plants both sweet or bitter cassava, the latter being of paramount in guyanese gastronomy. This resource is preserved in the country either in situ, in the Amazonic jungle and other mountain areas; like ex situ, in the germplasm banks of Kairuni and Ebini belonging to the National Institute of Investigation and Agricultural Extension which accounts with 87 accessions. The climate change and the population decline of the indigenous communities endangers the preservation in situ, that is why the National Institute of Investigation and Agriculultural Extension possesses the mission to develop the training activities to create sensibility to the local people to ensure the biological diversity of the Species and the culinary traditions are preserved.